Philosophy of Science (Scientific Method and Scientific Thinking Tools) - Fitri Nurlatifah Azzahra; Erni Hayanti; Teguh Pamuji; Bilal Zakawali Al-Fathoni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Scientific facilities are basically tools that assist scientific activities in the various steps that must be taken. Certain steps usually require certain facilities. For this reason, before we study the tools of scientific thinking, we should have mastered the steps in scientific activity. Scientific facilities are basically tools that assist scientific activities in the various steps that must be taken. Facilities are tools that help us achieve a certain goal, or in other words, scientific facilities have unique functions in relation to scientific activities as a whole. The purpose of studying scientific tools is to enable us to carry out scientific studies well, while the purpose of studying science is intended to gain knowledge that allows us to be able to solve our daily problems. In this case, the means of scientific thinking are tools for branches of knowledge to develop their knowledge material based on scientific methods.